Enhancing grammar competence of vocational school students through the Omygram learning chart - Ruhiana Idayu Abd Hamid; Tee Tze Kiong; Lutfiah Natrah Abbas; Noor Syuhaili Mohd. Rusly; Farah Najwa Ahmad Puad (Universitas Syiah Kuala, 2022)
Various methods and approaches have been used to support English learning. However, there is still a lack of information on how the grammar competence of vocational students can be improved in the Malaysian context. This study aims to build the Omygram learning chart and identify its effects on the achievement level of the students in Program Vokasional Menengah Atas (PVMA), or the upper-secondary vocational programme, on their English grammar competence. The study involved two secondary schools in Johor, Malaysia, employing a quasi-experimental design. A descriptive analysis from SPSS showed the increment in the mean score for the post-test of the treatment group of 5.58, higher than the control group (0.33) after the intervention was applied. The results of t-test showed no significant difference in achievement between pre-test and post-test for the control group [p = 0.504, (p 0.05)]. On the other hand, the result of the t-test for the treatment group showed a significant difference in achievement between the pre-test and post-test [p = 0.000, (p0.05)]. Students’ motivation after using the Omygram learning chart was also high. In conclusion, the development of the Omygram learning chart is proven to effectively increase students’ achievement in English. This confirms that developing learning aids improves students’ grammar competence and motivates them to learn the language better. As a result, the goal of producing a skilled workforce in TVET (Technical Education and Vocational Training) and possessing soft skills will be more achievable.